The Effect of Internal Branding, Affective Commitment, and Employee Empowerment on Employee Engagement Pt. Secure Parking Indonesia Mal Ciputra Jakarta - Beta Oki Baliartati; Netania Emilisa; Sherlly Handayani (Universitas Trisakti, 2021)
To be successful, a company must have Human Resources who can do their job well if employees have high engagement in the company for that required good internal branding, strong affective commitment to the company, and continuously improved employee empowerment. The purpose of this study was to analyze the effect of internal branding, affective commitment, and employee empowerment on employee engagement. This research was conducted on outsourced employees who are engaged in parking management service providers at PT. Secure Parking Indonesia, which is located in Ciputra Mall, Jakarta. The data collection technique used is a census of as many as 56 employees of PT. Secure Parking at Ciputra Mall Jakarta. This study uses quantitative research methods by testing the hypothesis, namely multiple linear regression, which previously tested the instrument in the form of testing validity and reliability. The results of hypothesis testing show that there is no positive effect of internal branding on employee engagement, there is a positive influence between affective commitment and employee empowerment on employee engagement.